EVOLVING CONNNECTIVITY PATTERNS OF BANJARESE KAMPUNGS AND RUMAH BUBUNGAN TINGGI (HIGH RIDGE-HOUSE) IN SOUTH KALIMANTAN RIVER NETWORKS - Laila Zohrah Zohrah (International Journal on Livable Space, 2019)
ABSTRACTThe objective of this study is to clarify the connectivity: spatial and physical patterns of Banjarese Kampungs in South Kalimantan river networks for the community of Rumah Bubungan Tinggi (RBT) or high ridge houses. It provides a basis for potential reconstructing a Banjarese Kampung in keeping with the sociocultural context. We investigated a total of an urban kampung (177 households) and 12 RBT groups (4 RBTs groups in 1 urban kampung and 8 RBT groups in 2 rural kampungs). We describe the development of kampung throughout the evolution of river networks, then analyze the formation of dwelling in the urban kampung and the changing of spatial composition in the kin-group. The discussion on the evolution river network is based on the reconstruction of waterway patterns from the 15th until the mid 20th century. Finally, the kinship interaction reveals the open-ended multifamily boundaries and the changing level of house connectivity such as rival kin-groupKeywords: Rumah Bubungan Tinggi (RBT) groups, kampung, connectivity, spatial composition, South Kalimantan